PWE-067 Healthcare resource utilisation and QOL in patients with UC by disease severity: iconic baseline data. (8th June 2018) - Haaren, Stijn van; Ghosh, Subrata; Peyrin-Biroulet, Laurent; Casellas, Francesc; O'Shea, Ciara; Lee, Wan-Ju; Pappalardo, Brandee; Petersson, Joel
Abstract : Introduction: ICONIC is a prospective, multi-country (n=33) observational study, assessing cumulative burden in adult ulcerative colitis (UC) patients (pts) under routine care. Assessments of healthcare resource utilisation (HCRU), disease severity and impact on quality of life will be captured at 6 month intervals through 2 years. This analysis evaluated baseline (BL) HCRU, work productivity, and quality of life among UC pts with different level of disease severity. Methods: Pts with early UC (diagnosed ≤36 months) were enrolled irrespective of disease severity or treatment. For this analysis, we evaluated pts stratified by physician assessment of disease severity into severe, moderate, mild and remission groups. BL characteristics described: Simple Clinical Colitis Activity Index (SCCAI), UC-related HCRU measured during the 6 months prior to study enrollment (i.e., visits to treating physicians or other IBD-associated healthcare professionals, emergency room (ER) visits, hospitalizations and hospital admissions for surgeries); Health Related Quality of Life (HRQoL), pt-reported employment/UC-related sick leave status and Work and Productivity Activity Index (WPAI:GH; including work time missed (absenteeism), impairment while working (presenteeism), overall work productivity impairment, and daily activity impairment domains). Results: A total of 1816 UC pts were enrolled; mean ±SD age was 38.5±14.6 years and 833 (45.9%) were female. At BL, 230 pts (12.7%) were in remission, 672 pts (37.0%) had mild UC, 668 pts (36.8%) had moderate UC, and 234 (12.9%) had severe UC. Compared to pts in remission, pts with moderate to severe UC had 1.8 to 2.6-fold higher rates of hospitalizations and 1.6 to 2.5-fold higher rates of ER visits over the past 6 months. Pt with moderate and severe disease were associated with lower SIBDQ scores and higher WPAI:GH domain scores (i.e., greater impairment on work productivity) than pts with mild disease or those in remission. 172 (9.5%) pts reported to be unemployed at BL. 183 (10.1%) reported sick leave at BL. Sick leave time ranged from <2 months (59.6%), 2–4 months (12.6%), >4 months (22.4%). Conclusion: The direct and indirect burden of UC is substantial, as measured by healthcare resource utilisation and work-life impact. Pts with moderate and severe UC not only were associated with higher rates of urgent care in hospitalisation and ER visits, but also with poorer quality of life, higher unemployment, sick leave and impaired work productivity than pts with mild UC or in remission. For pts with mild UC, despite comparable HCRU to pts in remission, increased impact on work productivity remains a concern.